PRESTASI BELAJAR BIOLOGI PADAKELAS II AKSELERASI DAN REGULER SMA NEGERI 3 SURAKARTA DITINJAU DARI CARA BELAJAR, MINAT BELAJAR DAN EMOTIONAL QUOTIENT (EQ) (STUDENT’S ACHIEVEMENT ON BIOLOGY OF THE STUDENT OF ACCELERATION CLASS OF SMA NEGERI III SURAKARTA, EMPHASIZED ON THEIR LEARNING METHOD, LEARNING MOTIVATION AND THEIR EMOTIONAL QUOTIENT (EQ)) - LILIK NUR HAMIDAH; SAJIDAN SAJIDAN; SUMANTO SUMANTO (Bioedukasi: Jurnal Pendidikan Biologi, 2006)
This is the descriptive-quantitative research which aimed to know the student achievement on biology which specify in a view point of their learning method, motivation and EQ. Acceleration class program of 2nd grade student of SMA Negeri III Surakarta was the object of this research. Clustered random salmpling was used to collect the data, which was held by questionaire and documentation. Analysis of Variance was used to analyze the data.The result showed that any learning method was suitable for the student of acceleration programs, since we know that they have the more prominent academic ability. Various EQ and learning motivation were occur, then can be concluded that EQ and learning motivation were still affected their achievement.This is the descriptive-quantitative research which aimed to know the student achievement on biologywhich specify in a view point of their learning method, motivation and EQ. Acceleration class program of2nd grade student of SMA Negeri III Surakarta was the object of this research. Clustered random salmplingwas used to collect the data, which was held by questionaire and documentation. Analysis of Variance wasused to analyze the data.The result showed that any learning method was suitable for the student of acceleration programs,since we know that they have the more prominent academic ability. Various EQ and learning motivationwere occur, then can be concluded that EQ and learning motivation were still affected their achievement.